Implementing effective salt reduction programs and policies in low- and middle-income countries: learning from retrospective policy analysis in Argentina, Mongolia, South Africa and Vietnam. Issue 3 (13th March 2022) - Webster, Jacqui; Santos, Joseph Alvin; Hogendorf, Martyna; Trieu, Kathy; Rosewarne, Emalie; McKenzie, Briar; Allemandi, Lorena; Enkhtungalag, Batsaikhan; Do, Ha Thi Phuong; Naidoo, Pamela; Farrand, Clare; Waqanivalu, Temo; et al.
Abstract: Objective: To understand the factors influencing the implementation of salt reduction interventions in low- and middle-income countries (LMIC). Design: Retrospective policy analysis based on desk reviews of existing reports and semi-structured stakeholder interviews in four countries, using Walt and Gilson's 'Health Policy Triangle' to assess the role of context, content, process and actors on the implementation of salt policy. Setting: Argentina, Mongolia, South Africa and Vietnam. Participants: Representatives from government, non-government, health, research and food industry organisations with the potential to influence salt reduction programmes. Results: Global targets and regional consultations were viewed as important drivers of salt reduction interventions in Mongolia and Vietnam in contrast to local research and advocacy, and support from international experts, in Argentina and South Africa. All countries had population-level targets and written strategies with multiple interventions to reduce salt consumption. Engaging industry to reduce salt in foods was a priority in all countries: Mongolia and Vietnam were establishing voluntary programs, while Argentina and South Africa opted for legislation on salt levels in foods. Ministries of Health, the WHO and researchers were identified as critical players in all countries. Lack of funding and technical capacity/support, absence of reliable local data and changes in leadership were identified as barriers to effective implementation. No country had a comprehensive approach to surveillance or regulation for labelling, and mixed views were expressed about the potential benefits of low sodium salts. Conclusions: Effective scale-up of salt reduction programs in LMIC requires: (1) reliable local data about the main sources of salt; (2) collaborative multi-sectoral implementation; (3) stronger government leadership and regulatory processes and (4) adequate resources for implementation and monitoring.